Auditor Negotiations: An Examination of the Efficacy of Intervention Methods - Trotman, Ken T.; Wright, Arnold M.; Wright, Sally (The Accounting Review, 2005)
Negotiations are a pervasive feature of the audit process (e.g., the resolution of proposed audit adjustments and disclosures). The results of such negotiations are of great importance to the capital markets, the client, and the auditor. The purpose of this study is to examine the effectiveness of three promising, pragmatic intervention methods for enhancing auditor negotiation performance: a role-playing intervention—assuming the client's position in a mock negotiation; a passive intervention—explicitly considering the client's interests and options; and a practice intervention—engaging in a mock negotiation prior to the client negotiation. We posit that the role-playing intervention will improve negotiation results, because this approach requires direct experience in considering and arguing the client's position and more cognitive effort in obtaining an understanding of the counterpart's position, a critical factor identified in the negotiation literature for successful performance. Forty-five audit managers and partners were provided a realistic case based on an actual scenario involving the potential writedown of inventory due to obsolescence. Participants were randomly assigned to one of three groups (role-playing, passive, or practice) and asked to negotiate the issue with a confederate playing the role of the CFO. Auditor conservatism and a large actual subsequent writedown suggest that a significant adjustment is warranted. The results indicate that the role-playing intervention method led to an enhanced negotiation outcome (greater writedown) compared to the passive and practice groups. Process improvements on a number of dimensions were also found, particularly for the role-playing group compared to the practice group.